Farmers' mental health: A longitudinal sibling comparison - the HUNT study, Norway - Magnhild Oust Torske; Johan Håkon Bjørngaard; Bjørn Hilt; David Glasscock; Steinar Krokstad (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVE: Studies of the mental health of farmers have been largely cross-sectional and possibly confounded. We performed a prospective cohort study as well as a sibling comparison to control for unmeasured confounding. METHODS: Our study included 76 583 participants aged ≥19 years from the Nord-Trøndelag Health Study [HUNT1 (1984-1986), HUNT2 (1995-1997) and HUNT3 (2006-2008)]. We used the Anxiety and Depression Index (ADI) and the Hospital Anxiety and Depression Scale (HADS) to measure symptoms of mental distress. We used logistic regression to investigate the association between occupation at baseline and symptoms of mental distress 11 years later and fixed effects conditional logistic regression to compare farmers with their siblings working in other occupations. RESULTS: In the prospective cohort study, farmers had similar odds of having symptoms of psychological distress and anxiety as other manual occupational groups. Among all the occupational groups in the study, farmers had the highest odds of having symptoms of depression [odds ratio (OR) 1.99, 95% confidence interval (CI) 1.55-2.55, reference group: higher grade professionals]. Compared with their farming brothers and sisters, siblings in other occupations had lower odds of having high depression (OR 0.70, 95% CI 0.55-0.89) and anxiety (OR 0.79, 95% CI 0.63-1.00) scores in 2006-2008. CONCLUSION: Farmers had higher odds of having high depression scores compared to both other occupational groups and their siblings who were not working as farmers, suggesting that working in agriculture may impact mental health.